2016
DOI: 10.1186/s12864-016-2571-z
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the interactome of the Ser/Thr Protein Phosphatase type 1 in Plasmodium falciparum

Abstract: BackgroundProtein Phosphatase 1 (PP1) is an enzyme essential to cell viability in the malaria parasite Plasmodium falciparum (Pf). The activity of PP1 is regulated by the binding of regulatory subunits, of which there are up to 200 in humans, but only 3 have been so far reported for the parasite. To better understand the P. falciparum PP1 (PfPP1) regulatory network, we here report the use of three strategies to characterize the PfPP1 interactome: co-affinity purified proteins identified by mass spectrometry, y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(48 citation statements)
references
References 36 publications
(27 reference statements)
3
45
0
Order By: Relevance
“…Surprisingly, by contrast to other eukaryotes, PfI3 is a PP1 activator in P. falciparum and it has an essential role in the growth and survival of blood stage parasites (Freville et al, 2012). A more recent study combined co-affinity purification followed by mass spectrometry (MS), yeast two hybrid (Y2H) screening and in silico analysis for P. falciparum proteins with RVxF motif, which is present in most PP1 regulators, to define the PfPP1 interactome (Hollin et al, 2016). This effort identified 186 potential PP1 interactors in P. falciparum, of which 35 have been validated as PfPP1 interactors in an ELISA based assay (Hollin et al, 2016).…”
Section: Pp1mentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, by contrast to other eukaryotes, PfI3 is a PP1 activator in P. falciparum and it has an essential role in the growth and survival of blood stage parasites (Freville et al, 2012). A more recent study combined co-affinity purification followed by mass spectrometry (MS), yeast two hybrid (Y2H) screening and in silico analysis for P. falciparum proteins with RVxF motif, which is present in most PP1 regulators, to define the PfPP1 interactome (Hollin et al, 2016). This effort identified 186 potential PP1 interactors in P. falciparum, of which 35 have been validated as PfPP1 interactors in an ELISA based assay (Hollin et al, 2016).…”
Section: Pp1mentioning
confidence: 99%
“…A more recent study combined co-affinity purification followed by mass spectrometry (MS), yeast two hybrid (Y2H) screening and in silico analysis for P. falciparum proteins with RVxF motif, which is present in most PP1 regulators, to define the PfPP1 interactome (Hollin et al, 2016). This effort identified 186 potential PP1 interactors in P. falciparum, of which 35 have been validated as PfPP1 interactors in an ELISA based assay (Hollin et al, 2016). However, further experimentation is needed to confirm their roles as PfPP1 regulators.…”
Section: Pp1mentioning
confidence: 99%
“…Functional and structural studies revealed that interactions between PP1 and its regulators are mediated by specific binding sites that are conserved throughout evolution, including the so called RVxF and SILK motifs (Wakula et al, 2003) (Huang et al, 1999). So far, about 200 regulators have been described in humans (Hendrickx et al, 2009) while 100 proteins potentially interact with PP1 in Plasmodium (Hollin et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…One recent study implemented all three methods in an effort to map the PP1 interactome in the malaria parasite Plasmodium falciparum . [53] Although this study used all three methods, the overlap between the hits from the different methods was quite poor, mainly due to the fact that their AP-MS protocol yielded too few putative interactors (only 6). Ideally, a work-flow will begin with a large-scale AP/IP-MS screen for endogenous PP1 complexes followed by targeted Y2H experiments to map the binary interactions among the proteins, and finally analyzed using bioinformatics both retrospectively (e.g.…”
Section: Mapping the Pp1 Interactomementioning
confidence: 99%